এরশাদের পতন ও সাহাবুদ্দীনের অস্থায়ী শাসন : কাছ থেকে দেখা - খান, মনজুর রশীদ
On the downfall of Hussain Muhammad Ershad, b. 1930, ex-president of Bangladesh and on the temporary administration of Sāhābuddina Āhamada, chief of the caretaker government in Bangladesh, 1990-91.